Business Information System for Workshop Using Rapid Application Development Method - Adrianto, Ananda Andra; Kurniawati, Ana; Jauhari, Amrin Fakhruddin (JITTER: Jurnal Ilmiah Teknologi dan Komputer, 2026)
The development of information technology is driving digitalization in various sectors, including the repair shop industry. Digitalization can improve efficiency, record-keeping accuracy, and service speed. However, many small to medium-sized repair shops still use manual systems, such as the Betawi Motor Service (BMS) workshop in Jatiasih, which records transactions, stock, and financial reports separately using Microsoft Excel. This method causes problems such as input errors, data duplication, difficulty monitoring stock in real time, and inaccurate financial reports. To overcome these obstacles, this study aims to design and build a website-based business information system using the Rapid Application Development (RAD) method. The RAD method was chosen because it supports rapid and iterative development through the stages of requirements planning, design, development, and implementation. The system has three types of users: admin, manager, and employee, with different access rights. The results of Black Box Testing and User Acceptance Testing indicate that all features function well. This system can be accessed through https://bengkelbms.zya.me and helps digitize the BMS Workshop's operations.